Politics as the Church's Business: William Temple's Christianity and Social Order Revisited - Brown, Malcolm (Journal of Anglican studies, 2007)
Christianity and Social Order was a creature of its time and, although influential over several decades, is challenged by today's plurality and globalization. Nevertheless, the ascendancy of Radical and Neo-Orthodoxy repeats imbalances of the Christendom Group which Temple was concerned to counter. Temple's greatest weakness for today is his failure to appreciate the trend towards profound social plurality, and its challenge to his strong idea of nationhood. However, today's global economy suggests that plurality must be held in tension with other aspects of the dominant market model. Temple's work reinforces important critiques of market economics, including scepticism about the alleged impossibility of moral agreement. This in turn suggests that total abandonment of Temple's Middle Axiom approach may be premature. A better-developed theology of correctives would reflect classic Christian vocabulary, cohere with Temple's approach, and offer a route toward the revitalization of the Anglican tradition of public theology.